Representasi Perempuan di Parlemen Indonesia - EVI NOVIDA GINTING (Politeia: Jurnal Ilmu Politik, 2011)
Since the political reform, there is an agenda to give Affirmative action for women in politics. The method is providing 30% quota for women. Is there any impact to the increase number of women in parliament? This study describes the number of women in parliament (2004 &2009). This study uses the behavioral approach. The data was collected with the study of literature and documents. The study found that the number of women in parliament increased after the 2009 elections. This is wonderful information, but this increase is still less. In 2004 there are 550 DPR RI seats, and the number of women only 61 or 11.09%. However, In 2009, the number of women increased to 18%. In DPD (the 2004 election), there are 27 member or 21,09%. Then after 2009 election the number of women increased to 27% member. The finding indicates that voters are not allergic to women candidates. In addition, women as candidates has demonstrat-ed its power to get votes.Keywords: Affirmative action, general election, representation of women.